Comparison of Efficacy of Fractional CO2 Laser with Intralesional Steroid Versus Intralesional Steroid Alone in the Treatment of Keloids - Ayesha Shafqat; Kehkshan Tahir; Fatima Bashir; Memoona Tahir; Anum Naveed; Ghazia Shaheen (Journal of Pakistan Association of Dermatologists, 2025)
Background: Keloids are abnormal wound responses characterized by deposition of excessive collagen and glycoprotein. They are distressing for most of the patients symptomatically and aesthetically. Intralesional steroids are the most commonly used treatment for keloids. Fractional CO2 laser is an emerging therapeutic option for keloids which can be used alone or as combination with other therapies. Objective: To compare the efficacy of fractional CO2 laser with intralesional steroid versus intralesional steroid alone in the treatment of keloids. Methods: Sixty patients were randomly assigned into two groups (30 patients each). After applying topical anesthesia to patients, Group A received fractional CO2 laser sessions followed by intralesional triamcinolone acetonide (TAC) with a gap of 5 mins every 4th week for total 4 months. Group B received Intralesional TAC alone every 4th week for total 4 months. Efficacy was assessed at the end of 4th session and was labelled if there was grade 3 or grade 4 improvement in width and height of keloid, degree of hypertrophy, dyschromia and texture of keloid using modified quartile score. Results: Total of 60 patients (30 in each group) were recruited. The mean age was 26.60 ± 5.52 years in group A and 29.76 ± 6.20 years in group B. We found that efficacy was 90% (n=27) in Group A and 66.6% (n=20) in Group B with (P-value-0.028). Conclusion: Our study results demonstrated that fractional CO2 laser in combination with intralesional TAC has better efficacy as compared to intralesional TAC alone, with a statistically significant difference (P-value-0.028).